Study the Chemical Compassion of Gallstone and its Relationship to Acute Cholecystitis - Ameerah M. Zarzoor (Journal of Global Pharma Technology, 2016)
All over the world cholelithiasis is a main reason of morbidity. Gallstones are public between the general people; many people are ignorant of their presence because they not commonly cause symptoms. The detached of this revision was to conclude the chemical conformation of gallstones and any relationship between the composition of the stone and initiation of acute cholecystitis. For 50 patients (13 males and 37 females), the chemical composition of gallstones was tested. (46 %) of the sample are in age groups (40-50) years old. A seventy four of study participants were female. In 50 gallstone, cholesterol stones 27 (54 %), mixed stone 20 (40 %) and pigment stones was 3 (6 %). The modifier of female: male was (5.3:1). The studying shown that Cholelithiasis occurrence in the age group 40-50 ( 23 cases) is maximum follow them 13, 9 and 5 cases for age groups 30-39, 51-61 and 62 years old and more respectively. About 62% of patients with cholelithiasis have acute cholecystitis Conclusion: In Al-Kut city cholesterol gall stones is great incidence as associated to mixed & pigmented gall stones and most patients with cholelithiasis have acute cholecystitisKeywords: Gall stone, Cholelithiasis, Cholesterol, Bilirubin, Calcium.